2014
DOI: 10.1016/j.neuron.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Four GABAergic Interneurons Impose Feeding Restraint in Drosophila

Abstract: Summary Feeding is dynamically regulated by the palatability of the food source and the physiological needs of the animal. How consumption is controlled by external sensory cues and internal metabolic state remains under intense investigation. Here, we identify four GABAergic interneurons in the Drosophila brain that establish a central feeding threshold which is required to inhibit consumption. Inactivation of these cells results in indiscriminate and excessive intake of all compounds, independent of taste qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 60 publications
5
83
0
1
Order By: Relevance
“…We therefore asked whether fluid ingestion is a critical step for both types of food cues to suppress starvation-induced hyperactivity. Mutant flies with overfeeding and overingestion phenotypes exhibit normal starvation-induced hyperactivity (27). Consistently, we found that certain concentrations (e.g., 200 mM) of sorbitol failed to suppress starvation-induced hyperactivity, but could nevertheless support fly survival, which must be accompanied Student's t test (C) and one-way ANOVA (F and H) were applied for statistical analysis.…”
Section: Significancesupporting
confidence: 68%
“…We therefore asked whether fluid ingestion is a critical step for both types of food cues to suppress starvation-induced hyperactivity. Mutant flies with overfeeding and overingestion phenotypes exhibit normal starvation-induced hyperactivity (27). Consistently, we found that certain concentrations (e.g., 200 mM) of sorbitol failed to suppress starvation-induced hyperactivity, but could nevertheless support fly survival, which must be accompanied Student's t test (C) and one-way ANOVA (F and H) were applied for statistical analysis.…”
Section: Significancesupporting
confidence: 68%
“…The AMMC has also been implicated in auditory processing suggesting this may be a generalized sensory processing center (Lai et al 2012, Tootoonian et al 2012, Vaughan et al 2014). In addition, a number of interneurons have been identified that modulate feeding in accordance with other competing behaviors or satiation state, suggesting complex central brain circuitry underlies innate feeding behavior (Marella et al 2012, Flood et al 2013, Mann et al 2013, Pool et al 2014). While much is known about the coding of sweet and bitter tastants by GRNs, and how both motoneurons and interneurons govern behavioral response to tastants (Gordon and Scott 2009, Manzo et al 2012), fewer studies have examined how gustatory information is processed and transferred to higher brain centers.…”
Section: Taste Processing In Drosophilamentioning
confidence: 99%
“…The fly brain contains only ~300 dopamine neurons (Nassel and Elekes 1992), composed of 20 distinct clusters that have been implicated in numerous memory modalities (Friggi-Grelin et al 2003) and innervate diverse brain regions including the mushroom bodies (MBs) and GNG (Marella et al 2012, Pool et al 2014). To identify whether dopamine neurons are required for aversive taste memory, Kirkhart and Scott (2015) silenced two populations of dopamine neurons, PAM and PPL1, through expression of the dominant negative GTPAse Shibire TS1 .…”
Section: Neuroanatomy Of Aversive Taste Memorymentioning
confidence: 99%
“…Thus, expressing GAL4 and FLP in two partially overlapping enhancer patterns removes GAL80 and allows GAL4 to activate a UAS-controlled transgene in the intersectional cells (Shang et al 2008;Bohm et al 2010;Pool et al 2014). Notably, this method requires four transgenes: 1) a ubiquitously expressed, FRT-flanked GAL80 cassette, 2) an enhancer-FLP line, 3) an enhancer-GAL4 line, and 4) a coding sequence of interest expressed under UAS control.…”
Section: Intersectional Techniques For Identifying Behaviorally Relevmentioning
confidence: 99%
“…In the case where a FLP-based method is being used, a GAL4 line that expresses in a neuron of interest is screened against a FLP enhancer trap library (Bohm et al 2010;Rezával et al 2012;Pool et al 2014). Although it is feasible that intersectional approaches can refine expression patterns to a single neuron (Figure 3a,b), in many cases the neurons of interest are not the only ones targeted by a particular spGAL4 or FLP/FRT pattern.…”
Section: Intersectional Techniques For Identifying Behaviorally Relevmentioning
confidence: 99%